El bloque de los movimientos naturales que se imparten en las clases de educación física y su incidencia en la iniciación del atletismo en los alumnos del 6to y 7mo grado de la escuela Simón Bolivar del cantón Célica primer quimestre 2013, provincia de Loja - Bustamante Jaramillo, Álvaro Francisco (2014)
This research work titled block natural movements taught in physical education classes and its impact on the initiation of athletics at students 6th and 7th grade school Simon Bolivar 2013 Celica Canton province of Loja the research question arises, how this affects the initiation block athletics either participation in school office or cantonal level students in the sixth and seventh years. The proposed objectives of the study are to establish the level of relationship between planning block natural motion with the initiation of track events in children 6th. And 7th, known as the lack of competence of track events does not reveal the skills for initiation of athletics at students in sixth seventh year of the School and propose a proposed internal competencies to promote the practice miniatletismo athletics in extracurricular hours in children 6th and 7th. School year Simón Bolívar Canton Celica. The literature review is part of the Physical Education and miniatletismo variables. To perform the research, a methodology according to the requirements of the investigation, the same character that is descriptive methods were used: deductive, inductive, analytical, descriptive, explanatory and statistical; information was collected through surveys applied to teachers and implementation of a pretest to students. The results were established in tables and graphs after tabulation and analysis and interpretation was conducted based on empirical data, discussion is based on the verification of the hypotheses coming as finding the lack of proper planning block games like half this if you allow the initiation of practice miniatletismo using methodologies that are related to age, Onsite qualitative, to prioritize the knowledge depth of the phenomena before the generalization of results, approaches are manifested particularly useful in the investigation, ie, studies that address problems whose systematic process is scarce finally alternative guidelines is proposed to allow improve the practice of mini athletics at Simon Bolivar School Canton Célica